INVESTIGATION OF THE INFLUENCE OF THE DESIGN FEATURES OF THE TURNING MACHINE ON THE IMPLEMENTATION OF THE MOVEMENT MODES OF THE ARRAY IN THE MIDDLE OF THE WORKING CAPACITY WITH COMPLEX SPATIAL MOVEMENT - ZALYUBOVSKYI, MARK; PANASYUK, IGOR; BLAZHENKO, MARIIA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
It is noted that the movement of the working array in the filling tanks with different types of movement can be carried out in cascade, waterfall, and mixed modes of movement. The characteristics of these modes of movement of the working array, which can be implemented in the working capacity that performs complex spatial movement of the rolling machine, are presented. Each mode of movement of the working array is the most favorable for the corresponding finishing felting technological operations. With the use of the automated design system "SolidWorks", analytical studies of the influence of the design features of the rolling machine with an additional movable rocker link with a horizontal axis of rotation on the implementation of the mass movement modes in the middle of the working capacity with complex spatial movement were carried out. It was established that the implementation of the modes of movement of the working mass in the middle of the capacity of the rolling machine depends on the angular speed of rotation of the drive shaft, the scale coefficient of the machine and the coefficient that characterizes the ratio of the distance between the axes of the working capacity to the distance between the axes of the fork of the machine. Mathematical expressions for determining the maximum angular speed of the drive shaft of the rolling machine type with an additional movable rocker link with a horizontal axis of rotation, which will correspond to the implementation of the necessary mode of movement of the working array, when it moves in a given capacity, are obtained. The obtained research results can be used at the stage of designing the appropriate felting equipment.
Keywords: rolling machine; working array; angular velocity